Local limit theorems for transition densities of Markov chains converging to diffusions - Konakov, Valentin; Mammen, Enno (Probability theory and related fields, 2000)
We consider triangular arrays of Markov chains that converge weakly to a diffusion process. Local limit theorems for transition densities are proved.
Gesehen am 13.02.2018